Decree No. 942 of the year 2014 canceling the ministerial decree No. 304 of the year 2014 in respect of the service and maintenance centers / Egypt. Ministry of industry, trade, and small & medium projects ; Translated by The middle east library for economic services. - Egypt. Ministry of industry, trade, and small & medium projects; The middle east library for economic services, translator. (2025)
Serial No. 93/2014